Metastatic small cell lung cancer presenting as acute appendicitis: a case report. Issue 3 (7th March 2023) - Connell, Louis; Ng, Ziqin; Tai, Wei Zhong; Allanson, Ben
Abstract: We present a case of extensive stage small cell lung cancer presenting as perforated appendicitis secondary to an appendiceal metastasis. This is a rare presentation with only six reported cases in the literature. Surgeons must be aware of unusual causes for perforated appendicitis as in our case the prognosis can be dire. A 60-year-old man presented with an acute abdomen and septic shock. Urgent laparotomy and a subtotal colectomy were performed. Further imaging suggested the malignancy was secondary to a primary lung cancer. Histopathology demonstrated a ruptured small cell neuroendocrine carcinoma in the appendix with thyroid transcription factor 1 positive immunohistochemistry. Unfortunately, the patient deteriorated due to respiratory compromise and was palliated day six postoperatively. Surgeons should consider a broad differential diagnosis for the cause of acute perforated appendicitis as this can rarely be due to a secondary metastatic deposit from a widespread malignant process.